EVALUATION OF THE INTERACTION OF PIPERINE WITH ANTIDEPRESSANT SERTRALINE AND ANALGESIC PENTAZOCINE, USING DIFFERENT ROUTES OF ADMINISTRATION IN ALBINO MICE - Atal, Shubham; Phadnis, Pradeep; Vyas, Savita; Gudsurkar, Gopal; Churihar, Ritesh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To evaluate the effect of piperine on the antidepressant activity of sertraline and analgesic activity of pentazocine and to explore the effect of using oral and parenteral routes of administration on the possible interactions. Methods: Piperine was isolated from commercially obtained Piper nigrum extract. Swiss albino mice of either sex were divided into 8 groups (n=6) receiving: 2% gum acacia (oral, intraperitoneally [i.p.]), standard drug (oral, i.p.), standard drug + piperine (oral, i.p.), piperine (oral, i.p.). Tail suspension test (TST) was used for antidepressant effect and Eddy's hot plate method for analgesic effect. Sertraline and pentazocine were used as standard drugs (5 mg/kg) and piperine at 10 mg/kg. Result: In the TST, piperine alone (both routes) decreased immobility time, but the effect was statistically insignificant. Both combination groups (oral and i.p.) showed significantly better activity compared to sertraline oral and i.p. groups, respectively (p<0.05). Oral combination showed activity comparable to i.p. combination (p>0.05). Piperine did not show any analgesic activity of its own (both routes). Piperine with pentazocine orally showed significantly better activity compared to pentazocine (oral) at 1, 2, and 4 hrs, and analgesia at 0.5 hr which pentazocine oral did not. Parenteral combination was significantly better than pentazocine (i.p.) group at 2 and 4 hrs and better than oral combination at 4 hrs. Conclusion: Piperine has potential to be used in combination with pentazocine due to its bioenhancing effect and with sertraline due to a potentiating/ additive effect which can help reduce dose and adverse effects of these drugs. Keywords: Piperine, Pentazocine, Sertraline, Albino mice, Bio enhancement, Potentiation.